The Implementation of Wall Chart Media to Improve Students’ Vocabulary Mastery in EFL Classroom - Mufidah, Zahratul Maujudatul; Khofifah, Kholifatul (Journal of Language Intelligence and Culture, 2024)
This study aims to improve the students’ vocabulary mastery using wall chart as a media. It was Classroom action research with two cycles. The procedures of each cycle were planning, acting, observing, and reflecting. The participants of this study consisted of one English teacher and 28 students of MTS Wahid Hasyim Balung, a totaling 29 participants. The data were collected quantitatively and qualitatively, namely observation classroom, interview, and vocabulary test. The findings showed that the students could improve their vocabulary mastery after using wall chart as the media in learning process. It can be seen that in cycle 1 the mean score of students was 72 and in cycle 2 was 79. The teacher also helps the students to correct the spelling and the pronunciation. The research result also showed that the wall chart was a good media for learning English vocabulary.